Correlative Analysis of Vertebral Trabecular Bone Microarchitecture and Mechanical Properties: A Combined Ultra-high Field (7 Tesla) MRI and Biomechanical Investigation. Issue 20 (15th October 2017) - Guenoun, Daphne; Fouré, Alexandre; Pithioux, Martine; Guis, Sandrine; Le Corroller, Thomas; Mattei, Jean-Pierre; Pauly, Vanessa; Guye, Maxime; Bernard, Monique; Chabrand, Patrick; Champsaur, Pierre; Bendahan, David
Abstract : Study Design: High-resolution imaging and biomechanical investigation of ex-vivo vertebrae. Objective: The aim of this study was to assess bone microarchitecture of cadaveric vertebrae using ultra-high field (UHF) 7 Tesla magnetic resonance imaging (MRI) and to determine whether the corresponding microarchitecture parameters were related to bone mineral density (BMD) and bone strength assessed by dual-energy x-ray absorptiometry (DXA) and mechanical compression tests. Summary of Background Data: Limitations of DXA for the assessment of bone fragility and osteoporosis have been recognized and criteria of microarchitecture alteration have been included in the definition of osteoporosis. Although vertebral fracture is the most common osteoporotic fracture, no study has assessed directly vertebral trabecular bone microarchitecture. Methods: BMD of 24 vertebrae (L2, L3, L4) from eight cadavers was investigated using DXA. The bone volume fraction (BVF), trabecular thickness (Tb.Th), and trabecular spacing (Tb.Sp) of each vertebra were quantified using UHF MRI. Measurements were performed by two operators to characterize the inter-rater reliability. The whole set of specimens underwent mechanical compression tests to failure and the corresponding failure stress was calculated. Results: The inter-rater reliability for bone microarchitecture parameters was good with intraclass correlation coefficients ranging from 0.82 to 0.94. Failure load and stress were significantly correlated with BVF, Tb.Sp, and BMD ( P  < 0.05). Tb.Th was only correlated with the failure stress ( P  < 0.05). Multiple regression analysis demonstrated that the combination of BVF and BMD improved the prediction of the failure stress from an adjusted R 2  = 0.384 for BMD alone to an adjusted R 2  = 0.414. Conclusion: We demonstrated for the first time that the vertebral bone microarchitecture assessed with UHF MRI was significantly correlated with biomechanical parameters. Our data suggest that the multimodal assessment of BMD and trabecular bone microarchitecture with UHF MRI provides additional information on the risk of vertebral bone fracture and might be of interest for the future investigation of selected osteoporotic patients. Level of Evidence: N /A